2002
DOI: 10.1523/jneurosci.22-08-03206.2002
|View full text |Cite
|
Sign up to set email alerts
|

Does Anticipation of Pain Affect Cortical Nociceptive Systems?

Abstract: Anticipation of pain is a complex state that may influence the perception of subsequent noxious stimuli. We used functional magnetic resonance imaging (fMRI) to study changes of activity of cortical nociceptive networks in healthy volunteers while they expected the somatosensory stimulation of one foot, which might be painful (subcutaneous injection of ascorbic acid) or not. Subjects had no previous experience of the noxious stimulus. Mean fMRI signal intensity increased over baseline values during anticipatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

22
219
1
3

Year Published

2003
2003
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 382 publications
(245 citation statements)
references
References 68 publications
(95 reference statements)
22
219
1
3
Order By: Relevance
“…Structures in the PFC are necessary to learn complex associations and may contribute to awareness of emotional feeling states (Lane et al, 1998). Neuroimaging experiments in which participants are asked to reflectively generate (Teasdale et al, 1999), monitor (Henson, Rugg, Shallice, Josephs, & Dolan, 1999), anticipate (Porro et al, 2002), attribute (Paradiso et al, 1999), or report on (Gusnard, Akbudak, Shulman, & Raichle, 2001) emotional states typically show heightened prefrontal, especially medial prefrontal, activation.…”
Section: The Neuroscience Of Evaluationmentioning
confidence: 99%
“…Structures in the PFC are necessary to learn complex associations and may contribute to awareness of emotional feeling states (Lane et al, 1998). Neuroimaging experiments in which participants are asked to reflectively generate (Teasdale et al, 1999), monitor (Henson, Rugg, Shallice, Josephs, & Dolan, 1999), anticipate (Porro et al, 2002), attribute (Paradiso et al, 1999), or report on (Gusnard, Akbudak, Shulman, & Raichle, 2001) emotional states typically show heightened prefrontal, especially medial prefrontal, activation.…”
Section: The Neuroscience Of Evaluationmentioning
confidence: 99%
“…In humans, different subregions of the PFC have a role in acute pain; the medial prefrontal cortex (mPFC) was found to be involved in signaling the unpleasantness of pain (3); the anterior cingulate cortex mediates the affective component of pain responses (4) and the placebo effect (5); and anticipation of pain is positively correlated with activity in both the anterior cingulate and mPFC (6). Lending support to the hypothesis that chronic pain involves cortical reorganization, functional MRI (fMRI) studies in patients with complex region pain syndrome type I (CRPS-I) and back pain have shown that the patients' real-time rating of perceived intensity of spontaneous pain is associated with novel activity in mPFC (7,8) when compared with activity patterns that correlate with rating of acute pain stimuli.…”
mentioning
confidence: 99%
“…The prefrontal cortex (PFC), anterior insula, and anterior cingulate cortex (ACC) are activated during the anticipation of pain, but their exact role in pain expectation remains poorly delineated (9)(10)(11)(12). Moreover, the neural mechanisms by which conscious predictions about the magnitude of pain influence the experience of pain remain poorly understood and largely unexploited in the treatment of pain.…”
mentioning
confidence: 99%